Rancang Bangun Alat Penjernih Air Tipe Portable Menggunakan Metode Nigel Cross - Malik, Abdul; Fiatno, Aris; Setiawan, Beny (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The earth's surface consists of 71% water, water itself has unique characteristics, both physical and chemical. The Kampar river basin has a direct influence on the quality of groundwater (wells) for the residents of Kampung Baru Salo Hamlet. This is because this area is directly adjacent to the Kampar river, ground water (wells) in every house of the residents of Kampung Baru Hamlet is used for daily needs such as consumption, bathing and washing. Along with rapid population growth, the need for clean water is also increasing. This is one of the problems that occurs in Kampung Baru Hamlet, namely the lack of groundwater (wells) that is clean and suitable for consumption. The research carried out by the author discusses how to design a portable water purifier that is efficient and uses easily available materials. This design was carried out using the Nigel cross method. Data collection was carried out by giving questionnaires to 25 respondents who experienced difficulties with clean well water (fit for consumption). Based on the results of the research that has been carried out, the researchers concluded that portable water purifiers can overcome the problem of lack of clean water that occurs in the community and also that the materials for making them are easy to obtain so that people can make them at home. Based on the results of consumption standard testing, the water produced from this filtration process meets the standard consumption requirements, namely 7 - 9 pH.